2012
DOI: 10.1007/s00420-012-0743-y
|View full text |Cite
|
Sign up to set email alerts
|

Lung function decline and blood lead among residents nearby to industrial complex

Abstract: PURPOSE: This study was to ascertain the risk factors of pulmonary function decline (forced expiratory volume in 1 s [FEV(1)], forced vital capacity [FVC]) among those exposed to lead in the vicinity of industrial complex. METHODS: In total, 263 men and women, aged over 30, were recruited from two cities during a 2-year follow-up. Spirometry testing was conducted first at baseline and then after 2-years of follow-up. The change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…There are quite a few studies investigating the association between exposure to lead and asthma, and therefore, the association is undetermined. Increased Pb blood levels are associated with bronchial hyperresponsiveness, total IgE and decrease in FEV 1 and FVC [16,17,25,68]. In a recent study the blood Pb level was associated with self-reported asthma [65].…”
Section: Leadmentioning
confidence: 96%
See 2 more Smart Citations
“…There are quite a few studies investigating the association between exposure to lead and asthma, and therefore, the association is undetermined. Increased Pb blood levels are associated with bronchial hyperresponsiveness, total IgE and decrease in FEV 1 and FVC [16,17,25,68]. In a recent study the blood Pb level was associated with self-reported asthma [65].…”
Section: Leadmentioning
confidence: 96%
“…HBM4EU-priority chemicals associated with asthma are diisocyanates, hexavalent chromium (Cr(VI)) (both cause specific sensitization), polyaromatic hydrocarbons (PAHs) and organophosphate insecticides [8,12,18,23,24]. The following chemicals are possibly associated with asthma: phthalates, per-and polyfluoroalkyl substances (PFASs), pyrethroid insecticides, mercury, cadmium, arsenic, lead and p-Phenylenediamine (p-PDA, a potential specific sensitizer) [10][11][12][13][14][15][16][17][19][20][21][22].…”
Section: Chemicals Associated With An Increased Risk Of Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have demonstrated that blood Pb and blood Cd levels were associated with lower lung function levels in adults. Whether this also holds for children (who are more susceptible) from e-waste recycling areas was not explored and therefore still unclear (Pak et al, 2012;Park and Lee, 2013;Oh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, this type of analysis has been rarely performed. For example, a study reporting the association between the Sihwa/Banwol IC and increased blood lead levels and reduced pulmonary function in nearby residents [ 16 ], and another study reporting the association between various IC areas and elevated urine cadmium concentrations and decreased bone mineral density in nearby residents [ 17 ] performed biomarker-based exposure assessments without verifying the causal relationship between the high biomarker concentrations and the pollutants released from the corresponding IC. A survey was conducted among the residents of the exposure areas and control areas as part of the IC Monitoring Project, but it was impossible to confirm whether the inter-area difference was ascribable to the IC using only the questionnaire-based cross-sectional correlation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%